A STUDY OF WEAPON USE IN ANCIENT HUMAN EVOLUTION - Kushwaha, Sadhna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The use of arms and weapons is considered to have started with the development of human civilization. Humans produced it for their own security. But with the passage of time, its form kept changing and developing. In which, in many civilizations of the world, there was development in many forms from weapons to metallurgy. Its development in India after the Puranic civilization, the description of the weapons of the Indus civilization, Gupta period, Maurya period, Mughal period, Rajput period, the time of kings and the Maratha Empire etc. underlines the history of India and the development of human civilizations developed here. The relation of weapons is basically found in Hindi language books, because weapons have always been highlighted as a violent tendency. But with the change of time, it became a medium of security, sovereignty, protection and collective development. The reference of which can be seen today in the technological era of information technology of the 21st century. In which, after the development of organized political, social structure between countries, the organizational tendencies of war are increasing institutionally. The main example of which can be seen in the form of the war between Central Asia and Ukraine Russia. Also, in the current scenario, killers are also being seen from the point of view of security psychology. Because in countries like India where hunger, poverty, unemployment and lack of basic facilities are prevalent, a large part of the GDP has been focused on buying arms and weapons in the arms race. In the context of the possibilities of development, this arms race will have to be reconsidered and highlighted. Because for the possibilities of sustainable and potential development, it is absolutely necessary for humans to remain on earth in a systematic way, its reverse is also equally relevant that it is extremely important for nature to remain for human development. Because in the current scenario, it is believed that the availability of nuclear weapons in the entire world is so high that the Earth can be destroyed 7 times.